The efficacy of a video-based marker-less tracking system for gait analysis. Issue 10 (27th July 2017) - Ong, Alex; Harris, Ian Sujae; Hamill, Joseph
Abstract: Most clinical gait analyses are conducted using motion capture systems which track retro-reflective markers that are placed on key landmarks of the participants. An alternative to a three-dimensional (3D) motion capture, marker-based, optical camera system may be a marker-less video-based tracking system. The aim of our study was to investigate the efficacy of the use of a marker-less tracking system in the calculation of 3D joint angles for possible use in clinical gait analysis. Ten participants walked and jogged on a treadmill and their kinematic data were captured with a marker and marker-less tracking system simultaneously. The hip, knee and ankle angles in the frontal, sagittal and transverse planes were computed. Root Mean Square differences (RMSdiff ) between corresponding angles for each participant's support phase were calculated and averaged to derive the mean within-subject RMSdiff . These within-subject means were averaged to obtain the mean between-subject RMSdiff for the relevant joint angles in the two gait conditions (walking and jogging). The RMSdiff between the two tracking systems was less than 1° for all rotations of the three joint angles of the hip and knee. However, there were slightly larger differences in the ankle joint angles. The results of this study suggest a potential application in gait analysis in clinical settings where observations of anatomical motions may provide meaningful feedback.